Towards developing a valid scoring tool for bronchitis during flexible bronchoscopy - Thomas, Rahul J.; Eg, Kah Peng; Masters, Ian Brent; McElrea, Margaret; Chang, Anne Bernadette (Wiley, 2018)
Background: A valid bronchoscopic scoring tool for bronchitis would be useful for clinical and research purposes as currently there are none in children. From 100 digitally recorded flexible bronchoscopies (FB), we related the various macroscopic features to airway neutrophil % to develop a FB-derived bronchitis score (BScoreexp). We aimed to develop a FB-derived bronchitis tool. Methods: FB recordings for six visualised features: secretions (amount and color) and mucosal appearance (erythema, pallor, ridging, oedema) based on pre-determined criteria on a pictorial chart were assessed by two physicians independently, blinded to the clinical history. These features were used to obtain various models of BScoreexp that were plotted against bronchoalveolar lavage (BAL) neutrophil % using a receiver operating characteristic (ROC) curve. Inter- and intra-rater agreement (weighted-kappa, K) were assessed from 30 FBs. Results: Using BAL neutrophilia of 20% to define inflammation, the highest area under ROC (aROC) of 0.71, 95%CI 0.61-0.82 was obtained by the giving three times weightage to secretion amount and color and adding it to erythema and oedema. Inter-rater K values for secretion amount (K = 0.87, 95%CI 0.73-1.0) and color (K = 0.86, 95%CI 0.69-1.0) were excellent. Respective intra-rater K were 0.95 (0.87-1.0) and 0.68 (0.47-0.89). Other inter-rater K ranged from 0.4 (erythema) to 0.64 (pallor). Conclusion: A repeatable FB-defined bronchitis scoring tool can be derived. However, a prospective study needs to be performed with larger numbers to further evaluate and validate these results.